Programa Nacional de Desenvolvimento Sustentável de Territórios Rurais (Pronat) no Território Noroeste Paulista: análise da participação dos atores sociais - Oliveira, Luciana Carvalho de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The process of territories' formation implemented by the Secretaria do Desenvolvimento Territorial - SDT (Territorial Development Office) of the Ministério do Desenvolvimento Agrário (Ministry of Agrarian Development) faces several obstacles regarding the different and complex realities in which they are inserted, besides operational and conceptual fragilities, resulting in a development marked by singularities in each Territory. This study had as an objective to analyze the implantation and development of Programa Nacional de Desenvolvimento Sustentável de Territórios Rurais - Pronat (National Program of Sustainable Development of Rural Territories), in Território de Desenvolvimento do Noroeste Paulista (Northwest Development Territory of São Paulo), between 2007 and 2014, focusing on participation of institutions and social actors. Besides the literature review, the research relied on three main instruments: field notebook, documental research and semi- structured interviews. From analysis of all the information generated it was found that advances and/or difficulties since the establishment of the Territory are related, but not exclusively, with the process of the social actors' participation, because this process is also influenced by financial resources and technical support offered by the government in terms of territorial development policies. It was found that the Pronat represented an advance for the Territory-NP, to propose an institutional arrangement and a methodology that encouraged the participation of different social actors in the discussion and execution of actions, even if participation has been uneven, however, with the persistence of some actors/institutions concentrated on the Executive Committee. Finally, there are some caveats to Pronat regarding the effectiveness of their concrete result to the development of the Territory, as this suffered from interruptions in the flow of financial resources, which ...

O processo de formação dos territórios implantados pela Secretaria de Desenvolvimento Territorial (SDT) do Ministério do Desenvolvimento Agrário enfrenta vários obstáculos relativos às diferentes e complexas realidades em que estão inseridos, além de fragilidades operacionais e conceituais, resultando em um desenvolvimento marcado por singularidades em cada Território. Este estudo teve como objetivo analisar a implantação e o desenvolvimento do Programa Nacional de Desenvolvimento Sustentável de Territórios Rurais (Pronat), no Território de Desenvolvimento do Noroeste Paulista, entre os anos de 2007 e 2014, com foco na participação das instituições e atores sociais. Além da revisão bibliográfica, a pesquisa recorreu a três instrumentos principais: caderno de campo, pesquisa documental e entrevistas semiestruturadas. A partir da análise do conjunto de informações geradas verificou-se que os avanços e/ou as dificuldades desde a implantação do Território estão relacionados, mas não exclusivamente, com o processo de participação dos atores sociais, pois também influenciaram nesse processo os recursos financeiros e técnicos oferecidos por parte do governo em termos de política de desenvolvimento territorial. Constatou-se que o Pronat representou um avanço para o Território-NP, ao propor um arranjo institucional e uma metodologia que estimularam a participação de diferentes atores sociais, na discussão e na realização de ações, ainda que a participação tenha sido irregular, porém com a persistência de alguns atores/instituições, concentrados na Comissão Executiva. Por fim, cabem ressalvas ao Pronat quanto à efetividade de seus resultados concretos para o desenvolvimento do Território, pois este sofreu com interrupções no fluxo dos recursos financeiros, os quais também são insuficientes para o desenvolvimento das ações, para o apoio à participação dos representantes da sociedade civil e ...
Keywords: Politicas publicas; Desenvolvimento rural - São Paulo (Estado) - 2007-2014; Participação social; Public policy